The Intertextuality of the Sufi Poetry A study in a poem by AbdulGhaniـ AlNabulsy - Sulaiteen, Wafik; Jalloul, Rayan (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research unseels Abdul GhaniAlnabulsy’s poem as an opposed poem for two other ones; which are the famous poem by Abdul Kareem Aljily and a poem by IbnAlfarid. That is to show the interrelation with in them through inducting the indicative parts which take it to a contractual domatic joint from one side, and to backtrace the formatic artistic methods which join them with the other’s poetry from the other side. The research has reached the fact that Alnabulsy’s sound, has interpenetrated with the sound of the antecedent poet; to lessen the sound of the belated poet in front of the old one, as if the uniqueness feature in his age was in the antecedence for who follows the an cestors’steps, to be the one who can be like the previous poets is the most remarkable one.